The Rhetoric of Supplication and Emotional Intelligence in Ibn Hajar al-ʿAsqalānī's Bulugh al-Maram - Daud Lintang; Sukron Kamil; Bambang Suryadi; Siti Amsariah; R. Yaniah Wardani (Al-Zahra : Journal for Islamic and Arabic Studies, 2026)
This study aims to analyze the asalib al-balaghah (rhetorical styles) found in selected prayers from Kitāb Bulūgh al-Marām by Ibn Ḥajar al-‘Asqalānī, focusing on three main branches of balāghah: al-bayān (figurative semantics), al-ma‘ānī (contextual semantics), and al-badī‘ (aesthetic language). This research also seeks to answer how the uslūb al-du‘ā (style of supplication) in Bulūgh al-Marām can influence emotional intelligence. This research uses descriptive-qualitative method and stylistic approach of balaghiyyah and generative transformative with the help of emotional intelligence theory. This research is a library research that searches for information through books, articles, and scientific journals. The primary source of this research is the book Bulugh al-Maram by Ibn Hajar al-‘Asqalani. The secondary sources are books and articles related to the theme of uslub al-balaghah and emotional intelligence. Data obtained from these two sources were analyzed using content analysis and comparative methods. The results show that the prayers are composed with a beautiful and rhetorical Arabic style, this beauty is seen in three elements of al-balaghah. First, the al-bayan element appears in the use of metaphors and parables that are able to evoke inner feelings. Second, the al-ma‘ani is seen from the sentence structure and word choice that is in harmony with the condition of the soul and feelings. Third, the al-badi'‘ element is present through the play of sound and the beauty of language styles that add emotional appeal. These three elements combine to create a prayer style that touches the heart and strengthens the spiritual connection between humans and God. This research also proves that asalib al-balaghah in these prayers such as al-tashbih, al-isti‘arah, al-kinayah, al- majaz, al- itnab, al-jinas, al-tibaq, al-saja’ are also factors in building emotional intelligence. The language style in these beautiful prayers is proven to instill the values of self-awareness (al-wa‘y al-dhati), self-control (dabt al-nafsi), self-motivation (al-tahfiz al-dhati), empathy (al-ta‘atuf) and social skills (al-maharat al-ijtima‘iyyah) which are fundamental aspects of emotional intelligence. Through field studies, this research also proves empirically that asa>li>b al-balaghah contained in prayers affects the psychology of its readers and the practitioners.